Sénèque, le stoïcisme et la monarchie absolue dans le De clementia - Gérard Salamon (Aitia : Regards sur la Culture Hellénistique au XXIe Siècle, 2011)
De clementia is a treaty of exhortation for guiding Nero on the road to good government by convincing him to practice clemency, in so far as it is considered as a cardinal virtue. But at a time when Stoicism in Rome seems bound by the figure of Cato to Republican values, this work also involves an internal debate in Stoicism. Seneca claims an orthodox Stoicism both to justify its acceptance of absolute monarchy and the prominent place that he grants to clemency, which is essential in this kind of political system. On the institutional level, Seneca seems to have solid argumentation ; as far as clemency is concerned, he can be regarded as seeking to change the doctrine, even if he continues to invoke frames of Stoicism. Historical events are enough to prove that Seneca did not convince, but it remains the case that De clementia is the work of a true Stoic.